Adsorption of UF6on Graphene Derivatives: a Computational Study of Conditions for 2D Enrichment. Issue 1683 (19th May 2014) - Koh, Yang Wei; Westerman, Kenneth; Manzhos, Sergei
ABSTRACT: We present a computational density functional theory study of UF6 adsorption on ideal as well as hydrogenated and fluorinated graphene. We show that (i) the isotopic splitting in the vibrational spectrum of UF6 observed in vacuum is largely preserved in the adsorbed molecules. The existence of several adsorption configurations with competing E ads leads to overlaps in the vibrational spectra of isotopomers, but isotopomer-unique modes exist on all three surfaces. (ii) The adsorption energy of UF6 is of the order of 1.2 eV on ideal graphene, 1 eV on graphane, and 0.1 eV on fluorographene, i.e. the adsorption strength is moderate and can be controlled by surface modification. (i) and (ii) mean that it may be possible to cause desorption of a selected isotopomer by laser radiation, leading to isotopic separation between the surface and the gas.